2016
DOI: 10.15294/jpfi.v12i2.4252
|View full text |Cite
|
Sign up to set email alerts
|

Development of Science Textbook Based on Scientific Literacy for Secondary School

Abstract: The purpose of this research is to develop scientific literacy-based science text books and to determine the characteristics, validity, readability, as well as the effectiveness of the textbooks.The study started with product development and then continued by feasibility test and readability test. Feasibility test was done with the respondent of lecturer and science teachers of VII, VIII, IX grade at SMP N at Central Java. Readability test used cloze test that filled by VII, VIII, and IX grade students at that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 8 publications
3
34
0
6
Order By: Relevance
“…The ratio of category of scientific literacy in the developed evaluation instrument was 37,50% : 25% : 18,75% : 18,75%. The results was agree with the ratio of category of scientific literacy 42% : 19% : 19% : 20% [4]. The suitability of science as a body of knowledge is the highest, but inexpediency appeared on the lowest, the category of science as a way of investigating is the lowest, the research explain that the lowest category is science as a way of thinking and interaction among science, technology and society.…”
Section: Characteristics Of Evaluation Instrument Based On Scientificsupporting
confidence: 84%
See 1 more Smart Citation
“…The ratio of category of scientific literacy in the developed evaluation instrument was 37,50% : 25% : 18,75% : 18,75%. The results was agree with the ratio of category of scientific literacy 42% : 19% : 19% : 20% [4]. The suitability of science as a body of knowledge is the highest, but inexpediency appeared on the lowest, the category of science as a way of investigating is the lowest, the research explain that the lowest category is science as a way of thinking and interaction among science, technology and society.…”
Section: Characteristics Of Evaluation Instrument Based On Scientificsupporting
confidence: 84%
“…Scientific literacy is important to knew by students in order to students' way to know the environment, health, economy, and other problems which are meet by modern society that's very depend on progress of technology and developed science knowledge [3]. Scientific literacy skills is showed on PISA (Programme for Student International Achievement) which is international study OECD (Organization for Economic Co- [4]. The results is needed on science learning evaluation in class.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of scientific literacy is assessing students' understanding of science content, science processes, and the context of science applications. Assessment of scientific literacy is not only oriented to mastering science material, but also to mastering life skills, thinking skills, and the ability to apply science in "real life" contexts (Rusilowati et al, 2016).…”
Section: Scientific Literacymentioning
confidence: 99%
“…Science is one of the subjects that occupy an important role in elementary education because science can be an important tool for students facing various challenges in the global era. Scientific literacy is the ability to understand and communicate science, and to apply scientific principles to solve problems (Rusilowati et al, 2016). The Program for International Student Assessment (PISA) found that the scientific literacy of Indonesian students are still below the international average.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study identify that the nine books of science in junior high school, have reflected the scientific literacy, but the proportion of the emergence of scientific literacy categories is not balanced. The category that looks dominant is science knowledge [15].…”
Section: Discussionmentioning
confidence: 99%